Designing Information Systems in Health Services Administration Medical Center Pamulang Permai II Tangerang. - Diana Meivita (Jurnal Sistem Informasi, 2005)
In writing this thesis discussed the design of Information Systems in Health Care Administration Medical Center Pamulang Permai II, Tangerang, where the administrative system that done at this clinic was using manual systems. So it required the design of administrative information systems in order to help alleviate and accelerate the work process, but it can streamline the data processing time. The first author analyzes a system running on these clinics, then the author tries to make the design a system that can simplify and accelerate the work system. Expected after the design made this health care system can provide the required information quickly and precisely.